STRATEGI DIVERSIFIKASI PENDANAAN DAN STABILITAS KEUANGAN SEKOLAH DASAR SWASTA DI JAWA TIMUR - Erika Agustiana; Rini Sriyanti; Yan Noviar Nasution (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze funding diversification strategies and their implications for financial stability in private elementary schools in East Java. The research employs a qualitative approach with a case study design conducted in a private elementary school in the Pandaan area. The study involves seven key informants selected purposively based on their strategic roles in school financial management. Data collection techniques include semi-structured interviews, participatory observation, and document analysis of financial reports from 2022 to 2025. The data are analyzed using thematic analysis, supported by financial ratio and trend analysis. The findings indicate that the implementation of funding diversification strategies has increased the proportion of non-routine income from 22.6% to 30.2%. However, monthly cash flow stability remains suboptimal, as reflected by a relatively high average coefficient of variation of 45.7%. This study provides an empirical contribution to the development of the Sustainable Education Financing (SEF) model in the context of private elementary schools in Indonesia. It also highlights the importance of integrating funding diversification strategies with cash flow risk management to ensure the financial sustainability of educational institutions.